2018
DOI: 10.1136/svn-2017-000080
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of diffusion, perfusion and functional MRI to the disconnection hypothesis in subcortical vascular cognitive impairment

Abstract: Vascular cognitive impairment (VCI) describes all forms of cognitive impairment caused by any type of cerebrovascular disease. Early identification of VCI is quite difficult due to the lack of both sensitive and specific biomarkers. Extensive damage to the white matter tracts, which connect the cortical and subcortical regions, has been shown in subcortical VCI (SVCI), the most common subtype of VCI that is caused by small vessel disease. Two specific MRI sequences, including diffusion tensor imaging (DTI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Microstructural damage detected by DTI precedes the development of WMH on T2-W FLAIR MRI. DTI parameters are more sensitive and serve as early markers of microstructural neurodegenerative changes in CSVD patients (Ye and Bai, 2018 ). It should also be noted that we included the spectrum of CSVD patients, rather than limiting the study to patients with specific diagnoses such as vascular cognitive dysfunction, with the purpose of generalizing the results to all patients with at least minimal CSVD load, regardless of the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Microstructural damage detected by DTI precedes the development of WMH on T2-W FLAIR MRI. DTI parameters are more sensitive and serve as early markers of microstructural neurodegenerative changes in CSVD patients (Ye and Bai, 2018 ). It should also be noted that we included the spectrum of CSVD patients, rather than limiting the study to patients with specific diagnoses such as vascular cognitive dysfunction, with the purpose of generalizing the results to all patients with at least minimal CSVD load, regardless of the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study on the FA and MD values of fibers related to the recovery of nerve function showed that the FA values of patients in the VCI group were considerably reduced ( P < 0.05), and the MD values related to each nerve fiber were considerably increased ( P < 0.05). The research results of scholars such as Ye and Bai [ 18 ] also found that multimodal CNN can detect part of the brain nerve damage in a timely and efficient manner in VCI patients. In addition, it can be correlated with the degree of neurological damage in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…MCI patients have hypoperfusion in bilateral parietal lobes [76], posterior cingulate cortex (PCC) [77] and precuneus [78], left (L) occipital lobe, and bilateral frontal and temporal lobes [79], compared to healthy controls (HC). A study also showed an increase in perfusion in the L hippocampus, [80] right (R) amygdala and basal ganglia [including a rostral head of the R caudate nucleus, ventral putamen, and globus pallidus] [81].…”
Section: Asl and MCImentioning
confidence: 99%